Persianism in antiquity - Strootman, Rolf; Versluys, Miguel John (Oriens et occidens, 2017)
The aim of this conference is to trace the origins of the concept of "Persia" in post-Achaemenid antiquity. It was in the Hellenistic and early Roman Near East that the idea of Persia fully developed. From the second century BCE, a varied cultural style developed that can best be described as "Persianism" -- the appropriation of an idealized past through the re-use or invention of imagery and concepts associated with that past